Flexible 3D structure of Bos taurus tyrosyl-tRNA synthetase suggests the existence of the hinge mechanism provided by conservative Gly353 at interdomain linker - Pydiura, N.A.; Kornelyuk, A.I. (Вiopolymers and Cell, 2012)
Mammalian tyrosyl-tRNA synthetase is composed of two structural modules: N-terminal catalytic miniTyrRS and non-catalytic cytokine-like C-terminal module connected by a flexible peptide linker. Till now, the 3D structure of any full-length mammalian TyrRS has not been solved by X-ray crystallography. The aim of this work was a homology modeling of 3D structure of full-lehgth B. taurus tyrosyl-tRNA synthetase. Methods. Homology modeling of TyrRS was performed by Modeller 9.1 package. Quality of the models was assessed using Biotech Validation Suite web-server. Results. Our BLAST search identified 34 % sequence homology between interdomain linker of TyrRS and linker of human c-Abl tyrosine kinase. In order to model the full-length TyrRS structure we assembled the models of three parts of the protein (N- and C- terminal domains and the linker) using Modeller 9.1 software. The best Abl-17 model structure was refined by energy minimization. Conclusions. High flexibility of the interdomain linker can generate multiple conformations of TyrRS. The hinge mechanism at interdomain linker may be provided by conservative Gly353. It is proposed, that due to the linker flexibility an open extended conformation of TyrRS could transform into closed conformations in the enzyme-substrate complexes.